Spontaneous Physical Activity Downregulates Pax7 in Cancer Cachexia - Coletti, Dario (Stem Cells Int, 2016)
Emerging evidence suggests that the muscle microenvironment plays a prominent role in cancer cachexia. We recently showed that NF-kB-induced Pax7 overexpression impairs the myogenic potential of muscle precursors in cachectic mice, suggesting that lowering Pax7 expression may be beneficial in cancer cachexia. We evaluated the muscle regenerative potential after acute injury in C26 colon carcinoma tumor-bearing mice and healthy controls. Our analyses confirmed that the delayed muscle regeneration observed in muscles form tumor-bearing mice was associated with a persistent local inflammation and Pax7 overexpression. Physical activity is known to exert positive effects on cachectic muscles. However, the mechanism by which a moderate voluntary exercise ameliorates muscle wasting is not fully elucidated. To verify if physical activity affects Pax7 expression, we hosted control and C26-bearing mice in wheel-equipped cages and we found that voluntary wheel running downregulated Pax7 expression in muscles from tumor-bearing mice. As expected, downregulation of Pax7 expression was associated with a rescue of muscle mass and fiber size. Our findings shed light on the molecular basis of the beneficial effect exerted by a moderate physical exercise on muscle stem cells in cancer cachexia. Furthermore, we propose voluntary exercise as a physiological tool to counteract the overexpression of Pax7 observed in cancer cachexia.